2021
DOI: 10.3390/ani11113285
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Components for Growth, Morphology, and Flesh-Quality Traits of Meagre (Argyrosomus regius) Reared in Tank and Sea Cage

Abstract: Meagre (Argyrosomus regius) plays an important role in the aquaculture system, with the potential for diversification of European aquaculture, and is characterized by its fast growth rate, low feed conversion ratio, and the high quality of the product. Focusing on the relevance of meagre, the aim of the study was to analyze growth performance, fish morphology, and flesh composition phenotypically and genetically to be considered as a strategy in a breeding program. For this purpose, 633 fish were raised in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…In the first, genetic factors may still influence the chemical diversity that is measured from cultivated plants. However, in the second method of clonal propagation, the elimination of genetic diversity across replicates is the key to understanding the phenomena of chemical phenotypic plasticity, and obviously, the mechanisms of chemodiversity [36,37]. Thus, clonal propagation is used in the current study as the chosen method to answer the question: "Is clonal chemical heritability a crucial factor for the conservation of chemical and chemodiversity characteristics of Piper foliar essential oils in controlled cultivation?"…”
Section: Introductionmentioning
confidence: 99%
“…In the first, genetic factors may still influence the chemical diversity that is measured from cultivated plants. However, in the second method of clonal propagation, the elimination of genetic diversity across replicates is the key to understanding the phenomena of chemical phenotypic plasticity, and obviously, the mechanisms of chemodiversity [36,37]. Thus, clonal propagation is used in the current study as the chosen method to answer the question: "Is clonal chemical heritability a crucial factor for the conservation of chemical and chemodiversity characteristics of Piper foliar essential oils in controlled cultivation?"…”
Section: Introductionmentioning
confidence: 99%
“…The application of SNP genetic markers to breeding is particularly valuable for difficult traits or those that cannot be measured in the selection candidates (e.g., disease resistance and fillet quality), in which the accuracy of the estimated breeding values can improve [4,5]. However, for other traits associated with aquaculture production with medium-high heritability, such as growth [21], the accuracy for estimated breeding values using a pedigree-based approach or genomic prediction is expected to be similar [41]. Furthermore, despite the fact that the cost of SNP genotyping has been dramatically reduced in the last few years, the cost of genotyping with microsatellites (8-10 markers) has been estimated to be two to three times cheaper compared to SNPs (150-200 markers) when they are used for parental assignments: EUR 3 for microsatellites versus EUR 7-11 for SNPs, not including DNA extraction.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…To date, in the case of meagre (Argyrosomus regius), no microsatellite marker panels have been developed, although several specific and interspecific microsatellites have been used in several works [10][11][12][13]17], and only a few studies [18][19][20] showed the multiplex they used for the parental assignment. Vallecillos et al [21] developed a panel of markers similar to this study but with some minor modifications. Several multiplex PCRs for parental assignment have been described for gilthead sea bream [22][23][24], for long-snouted seahorse [25], and recently for white-leg shrimp [26] and for Crassostrea hongkongensis [6].…”
Section: Introductionmentioning
confidence: 99%
“…The main producing countries in the Mediterranean area are Egypt, Turkey, Spain, and Greece, which accounted for 64.9%, 14.2%, 10.6%, and 6.5% of the total production in 2021, respectively [3]. One of the main characteristics of meagre is its fast growth rate (about 800-1000 g in 18 months) [4], with a low feed conversion ratio of 0.9-1.2 [5], a low fat content in fillet (about 1-3%), a good attractive shape as a whole fish product and it has high processing yield power [6]. Variables such as growth, feed efficiency, and product yield are very important for the meagre industry, as they add great value to both the production and the economic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The phenotypic and genetic variation in various product quality and yield traits have been estimated in salmon [14][15][16], Tilapia [17,18], sea bass [19], and gilthead seabream [20][21][22]. To the best of our knowledge, no work has been carried out on the genetic components related to other characteristics different from growth traits [6,23], which indicates a significant gap in the understanding of the genetic basis of the external morphology and yield traits in meagre.…”
Section: Introductionmentioning
confidence: 99%